PERGESERAN MAKNA DALAM BERITA TENTANG SAMPAH DI GORIAU (Meaning Shift of Garbage News in GoRiau) - Raja Saleh (Kantor Bahasa Sulawesi Tenggara, 2017)
This study aims at obtaining kinds of meaning shift that exist in garbage news in GoRiau and getting to know words that undergo meaning shift. The data of this study are taken from the news about garbage released by GoRiau, an online media. The data are collected by downloading garbage news in GoRiau online media. Based on the data collected, there are 34 news in GoRiau related to garbage. After downloading the data, they are analyzed by applying some steps, namely 1) identifying each news that undergoes meaning shift, 2) reducing the news that do not undergo the meaning shift, 3) classifying each word that undergoes meaning shift based on the type of meaning shifts, 4) describing each meaning shift qualitatively and comparing it with its definition in Kamus Besar Bahasa Indonesia (KBBI). The result of this study shows that there are all of meaning shift types in the news related to garbage in GoRiau.com. The meaning shifts are widening meaning, narrowing meaning, amelioration, pejorative, synecdoche, and association.